Diversified plasmonic metallic nanostructures with high aspect ratio based on templated electrochemical deposition. (1st May 2022) - Pan, Ruhao; Liu, Qiulin; Li, Guodong; Yang, Yang; Geng, Guangzhou; Li, Chensheng; Yan, Junxiang; Zhang, Zhongshan; Zhao, Huaizhou; Gu, Changzhi; Li, Junjie
Abstract: Metallic high aspect ratio (HAR) nano-architectures provide new opportunities for a series of plasmonic devices due to their additional controllable degrees in height space compared to 2D patterns, but there is no efficient way that suitable for the rapid fabrication of large area HAR structures limited by the processing ability of traditional methods. Here in this work, we have developed a templated electrochemical deposition (ECD) method to fabricate various HAR metallic nano-structures for diversified plasmonic devices. The templated ECD method is based on the ECD filling of the nanopores that are fabricated by electron beam lithography. With this templated ECD method, numbers of HAR architectures including nanorods, nanofins and even mushroom-like structures, which have a line width as small as 100 nm and the aspect ratio up to 10:1, are established over a large scale. What is more, by simultaneously considering the designed layout and edge effect, sub 10 nm nanogap arrays are prepared, whose aspect ratio reaches 100:1 and the gap width reduces to 5 nm. Due to the extreme light confinement ability brought from Fabry–Perot resonance, the HAR nanogaps can be treated as a surface enhanced Raman scattering (SERS) substrate. Finite domain time difference simulation shows that fan-like 10 nm nanogap with a height of 700 nm has the largest light enhancement factor (EF). The configuration optimized nanogap is capable for the sensing of rhodamine 6G with a 10 −9 M concentration. And the SERS EF of the nanogap is calculated to be 4 × 10 6, indicating the ultrasensitive molecular detection ability of the HAR nanogap. The templated ECD method not only brings a new chance for the construction of HAR metallic 3D structures, but also opens up a new horizon for the design of a series of plasmonic devices.